AIEE-active V-shaped fused-biscoumarins: synthesis, photophysical and electroluminescence properties. (25th November 2022) - Li, Debao; Li, Peiying; Zhao, Yuling; Su, Ruige; Guo, Yongchun; Su, Wenming; Yu, Tianzhi
Abstract : Three AIEE-active V-shaped fused-biscoumarin derivatives were prepared and their potential for application in OLED was explored. Abstract : V-shaped fused-biscoumarins have attracted considerable attention due to their interesting photophysical properties derived from the π-extended molecular frameworks, which could have the opportunity to be used in constructing optoelectronic materials. However, V-shaped fused-biscoumarins as electroluminescence materials easily suffer from aggregation-caused quenching (ACQ) in the solid state due to the presence of a large conjugate plane of the V-shaped fused-biscoumarin framework. To suppress the aggregation-caused emission quenching as well as increase the hole-transporting capability, three AIEE-active V-shaped fused-biscoumarin derivatives, namely, CC-TPA, CC-TPE and CC-TriPE, were successfully designed and synthesized by the introduction of triphenylamine (TPA), tetraphenylethene (TPE) and triphenylethene (TriPE) groups into the V-shaped fused-biscoumarin core. These compounds exhibited strong green emission in CH2 Cl2 solution and yellow or red emission in thin solid films and displayed good thermal stability. Moreover, solution-processed doped devices with a configuration of ITO/PEDOT:PSS (30 nm)/PVK:PBD (7 : 3 wt%):CC derivative ( x wt%) (30 nm)/TPBi (35 nm)/Liq (2 nm)/Al (200 nm) were fabricated by the solution processing method, among which the CC-TPA -based doped device exhibited a maximum luminance ( L max ) of 3054 cd m −2, a maximum current efficiency (CEmax ) of 6.81 cd A −1 and a maximum external quantum efficiency (EQEmax ) of 2.13%, respectively.